Enhanced Digitized Version of K. Mühlenbachs’ Dictionary of the Latvian Language. - Grasmanis, Mikus; Nešpore-Bērzkalne, Gunta (Digital Humanities in the Nordic & Baltic Countries Publications (DHNB Publications), 2025)
The Dictionary of the Latvian Language [Latviešu valodas vārdnīca] is a unique general scientific dictionary of the Latvian language, which was started in the 1880s by Kārlis Mühlenbachs (1923-1932), then edited, supplemented, and completed by Jānis Endzelīns and Edīte Hauzenberga-Šturma (1934-1946). It is both an explanatory and a translation dictionary with features of an etymological and synonym dictionary (Nespore et al. 2006). In 1994, the digitization of the dictionary and its additional volumes was started at the Institute of Mathematics and Computer Science, University of Latvia. In 2002, the electronic version of the dictionary (MEV) was published. It contained 132,718 entries. To make the dictionary more accessible, in 2024-2025, the MEV application was modernized and integrated with the Tezaurs.lv platform (Grasmanis et al. 2023; Mīlenbaha-Endzelīna vārdnīca 2000-2025). The article discusses the digitization process and methods of the resource, as well as outlines directions for future work.